An Analysis of Humanitarian Military Intervention in Nigeria: Focus on Saving Victims or Defeating Boko Haram? - Tiffany Setyo Pratiwi (Department of International Relations, University of Mataram, 2020)
ABSTRACT This paper discusses the humanitarian intervention in Nigeria because the Boko Haram’s attack. Humanitarian intervention was carried out because there had been gross human rights violations in an area and the government's inability to solve them. Boko Haram attack has caused a humanitarian crisis in Nigeria. Unfortunately, Nigeria has been unable to solve the problem. Boko Haram is a separatist group that wants to replace Nigeria’s legitimate government to Sharia Law. Thus, humanitarian intervention is needed. This paper will explain three sub chapters of the discussion, such as: First, the political and economic conditions in Nigeria. Second, process of Boko Haram attack. Third, humanitarian intervention efforts in Nigeria carried out by international actors, such as: The African Union, some countries in Africa, the United States and some international humanitarian agencies. The research method used in this study is a descriptive qualitative method. Data sources from literature and internet studies. This paper finds that the humanitarian intervention consists of a military approach and a socio-economic approach. In 2020, humanitarian interventions focus on recovery in education, health issues, and assisting the shelter of refugees.